Analisis Pengembangan dan Pemasaran Digital pada Noon Villa Bali Ditinjau Dari Kelayakan Bisnis (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study analyzes the business feasibility of Noon Villa Bali from its digital development and marketing aspects. The fierce competition in Bali's tourism industry post-COVID-19 pandemic serves as a crucial background, driving the need for optimizing digital strategies. Using a descriptive qualitative method, this research examines five aspects of business feasibility: legal, marketing, technical, management, and financial. The results show that Noon Villa Bali is, overall, considered feasible. The marketing, technical, and management aspects meet the feasibility criteria. However, the legal aspect is not yet fully feasible as vital permits like the Business Trading License (SIUP) and Accommodation Health Certificate are still in process. Financially, the investment is also declared feasible based on the analysis of Payback Period, Net Present Value, Profitability Index, Internal Rate of Return (IRR), and Average Rate of Return (ARR). In conclusion, although some legal requirements need to be completed, Noon Villa Bali's investment and digital strategy are generally feasible for development. It is recommended that management prioritize the completion of permits, optimize digital marketing, and maintain the product's uniqueness as a key competitive advantage.